TERAPIA INTERCEPTIVA DE LA MORDIDA ABIERTA EN DENTICIÓN MIXTA: REJILLA LINGUAL TIPO GARFIO VERSUS ESPOLONES. REPORTE DE CASO - Juárez Pacheco, María Alejandra (2025)
Objective: To describe the interceptive treatment performed in two mixed-dentition patients with functional anterior open bite, using two different approaches: a hook-type lingual crib combined with rapid maxillary expansion, and bonded tongue spurs combined with a 4×2 appliance. Case report: Two female patients aged 7 and 8 years, respectively, were diagnosed with anterior open bite, atypical swallowing with type II tongue interposition, and anterior tongue thrust. The patient in Case 1 also presented a 5-mm transverse maxillary deficiency and was treated with a hook-type lingual crib soldered to a Hyrax expander, followed by an active expansion phase and a passive retention period. In Case 2, with a 4-mm transverse maxillary discrepancy, tongue spurs were bonded to the palatal surfaces of the maxillary incisors and combined with a 4×2 appliance and a sequence of stainless-steel archwires (.012” to .018”). Both treatments incorporated myofunctional therapy focused on tongue repositioning during swallowing, phoneme articulation training, and muscular strengthening. Total treatment time was approximately eight months, with progressive improvement of the overbite observed from the third month onward in both cases. Conclusion: Both interceptive approaches the hook-type lingual crib and the bonded tongue spurs proved effective in correcting anterior open bite in mixed dentition, achieving adequate control of tongue interposition and clinically significant improvement of the overbite. Rapid maxillary expansion was beneficial in the case presenting a transverse discrepancy, whereas the 4×2 appliance optimized alignment in the second case. The incorporation of myofunctional therapy enhanced orofacial function and contributed to treatment stability.